Experimental investigation on laser ablation of C/SiC composites subjected to supersonic airflow. (May 2019) - Wang, Jiangtao; Ma, Yuzhao; Liu, Yuwen; Yuan, Wu; Song, Hongwei; Huang, Chenguang; Yin, Xiaowei
Highlights: The laser ablation mechanisms of C/SiC composites under the supersonic airflow environment are revealed. Quantitative experimental data on laser ablation of C/SiC composites in supersonic airflow are provided. Systematical comparisons on differences of ablation characteristics between static and airflow environment are proposed. Abstract: Continuous wave laser ablation behavior of C/SiC composites subjected to supersonic airflow, as well as in static air environment, is investigated experimentally. Ablation morphology and microstructure of the ablation region are measured by 3D digital microscope system and profiling system, respectively. Effects of supersonic airflow on the ablation morphology and ablation rates of the C/SiC composite are analyzed. Experimental results indicate that the mechanical erosion by supersonic airflow increases the ablation rates and smoothens the ablation surface. Many carbon fibers are left at the edge of center region due to the cooling effect of the supersonic airflow. The laser ablation behavior of C/SiC composites in supersonic airflow is attributed to the combined effect of convective cooling and mechanical erosion.